ANALYSIS OF THE MAIN COMPONENTS OF A SUSTAINABLE EDUCATIONAL ECOSYSTEM - Kovshar, O.V. (SWorld-Ger Conference proceedings, 2025)
The sustainability of the educational ecosystem is a key aspect of the country's development in a changing world. The proposed article attempts to systematize scientific ideas about the development of education at the present stage, to outline the nature